Design And Development Of A Portable Alcohol Testing Device For Motorists - Saputri, Fahmy Rinanda; Gregorius Radithya, Linus (Publisher Cv. Inara, 2023)
This research aims to design and develop a portable alcohol testing device that can be used to check whether prospective drivers have consumed alcohol before driving. The device is designed with the goal of improving road safety by reducing the risk of accidents caused by intoxicated drivers.In this study, we used the Figaro TGS 2620 alcohol sensor. The device is also equipped with a 16x2 LCD that displays test results directly and accurately. Additionally, we added indicators in the form of LEDs and a buzzer for signaling. The device we designed utilizes an Arduino UNO microcontroller.The test results and evaluations indicate that the portable alcohol testing device can respond to changes in alcohol levels around the sensor. When subjected to a non-alcohol condition, the device shows an average voltage reading of 0.69 V, whereas when subjected to the presence of alcohol, the device exhibits an average voltage reading of 3.97 V.